Prosedur Pengurusan Perpanjangan Sertifikat Keselamatan Kapal pada Kantor KSOP Kelas 1 Tanjung Balai Karimun oleh PT. Pelayaran Padimas Global Tanjung Balai Karimun: Penelitian - Meriah Kita Deliani; Anggi Br Tarigan (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The procedure for extending a Ship Safety Certificate plays a crucial role in ensuring the legality, seaworthiness, and operational safety of ships. This study analyzes the administrative and technical stages of certificate extension implemented by PT Pelayaran Padimas Global at the Class I KSOP Tanjung Balai Karimun through a descriptive qualitative approach with observation, document analysis, and literature review. The results indicate that the extension process includes application submission, document verification, physical inspection of the vessel by the Maritime Inspector, and issuance of a new certificate in accordance with applicable safety regulations. The main documents required include the previous certificate, inspection report, and proof of VAT payment, although obstacles such as limited inspection schedules, service constraints, and applicants' lack of understanding of the requirements are still encountered. Although the procedure complies with IMO standards and national maritime law, improvements are needed through system digitization, strengthening human resource capacity, and more transparent coordination to improve the efficiency, compliance, and quality of maritime certification governance in Indonesia.